Model of Character Education for College Students in the Era of VUCA - Burhan Nudin; Awliya, Wizarati; Prayesti, Tyas; Binti Abd. Malik, Nur Zakiyah; Binti Zaki Yudin, Hazwa Izatti; Binti Juhari, Anisah Iffah; Dwi Saputra, Kurniawan (Universitas Islam Indonesia, 2023)
With the presence of the fourth industrial revolution, humanity is faced with an increasingly Volatile, Uncertain, Complex and Ambiguous (VUCA) era. In such period, besides knowledge and skills, individuals are also required to embody strong character to confront the unpredictable challenges. This study aims to analyse character education for Indonesian and Malaysian Muslim college students in the VUCA era. This research uses qualitative approach with descriptive method and purposive sampling technique. The research has been conducted at Universitas Islam Indonesia (UII) and Universiti Kebangsaan Malaysia (UKM). Subject of this research were lecturers at UII and UKM. Data collection techniques include interviews, observation, and documentation. The data analysis method uses an interactive model. This study reveals that they are similarities as well as differences in the model of character education in UII and UKM. Lecturers in both UII and UKM observe the severe importance of character education for muslim college student in VUCA era. However, while lecturers in UKM emphasis on teaching technical preparation, UII lecturers inclined towards more personal approach and intense communications.